HAMILAKIS, Yannis. The Nation and its Ruins: Antiquity, Archaeology, and National Imagination in Greece, (Classical Presences). Oxford University Press, 2007. 352 pp. Reeditado em 2009. - Dagios, Mateus (Em Tempo de Histórias, 2012)
HAMILAKIS, Yannis. The Nation and its Ruins: Antiquity, Archaeology, and National Imagination in Greece, (Classical Presences). Oxford University Press, 2007. 352 pp. Reeditado em 2009.